Literasi Budaya Belis dalam Pernikahan Masyarakat Flores Desa Kusu Manggarai Barat Nusa Tenggara Timur - teguh hidayatul rachmad; yohanes probo dwi sasongko (Jurnal Iswara : Jurnal Kajian Bahasa, Budaya, dan Sastra Indonesia, 2024)
Marriage in the belis tradition in East Nusa Tenggara (NTT), has moral and cultural values that are broad and deep enough to be learned together. In the belis tradition, when a marriage couple is about to have a traditional wedding. Both prospective brides and grooms must have a good understanding of what they are doing when they carry out the belis tradition in the marriage. The study of belis culture does require a good understanding in its application, especially when it clashes with culture. The belis tradition can be seen as a way of making prospective couples who are getting married think twice before deciding to use the tradition. Not only is there a certain amount of material or nominal amount that must be prepared, the existence of certain objects or items that can and should be considered as dowry requires each couple to provide these materials and objects properly. Not to mention the existence of other agreements and offers, which of course can be understood. Marriage in the NTT tradition, with the culture of belis, is a phase for each young couple to prepare themselves to enter a new life in their life journey. The belis tradition is a pattern of life in the NTT community that can be used as one of the characteristics inherent in the traditions of our society. with cultural wealth that is certainly inherent and stored in it as a whole.